(untitled) (World Bulletin of Management and Law, 2022)
The objective of the research is to demonstrate the role of the integration of financial and non-financial information in predicting financial failure by banking units. The study examined a sample of 10 banks listed on Iraq’s stock market for the period 2009 to 2013. The independent variable was measured through financial and non-financial information disclosed by banks in their annual financial reports in agreement with several studies while the dependent variant was measured through the Z-Sherrod-1987 model), in agreement with several studies. The statistical program (SPSS) was used to know and explain the direction of the relationship (association) and the effect (decline) between the study variables, and the study found that there was no moral effect of disclosure of financial information in predicting financial failure despite its importance, while there is a moral effect of integrating financial disclosure